Reformulation of The Criteria for Determining the Wages of Micro, Small and Medium Enterprise Workers from The Perspective of John Rawls' Justice Theory - Efendi, Lutfi; Barthos, Megawati (Journal Of Social Science (JoSS), 2025)
This study analyzes changes in wage arrangements for micro and small business workers/laborers in the latest regulations, including the Job Creation Law, PP No. 7 of 2021, and PP No. 51 of 2023, using a normative legal approach and John Rawls' distributive justice theory. The study results show that, although the regulation provides flexibility for employers, there are still gaps in injustice due to weak monitoring mechanisms and the low bargaining power of workers. This regulation does not completely fulfill the principle of distributive justice, so a policy reformulation is needed that better protects micro and small business workers/laborers, such as setting sector-based minimum wage standards and strengthening monitoring mechanisms and legal protection. The application of Rawls' principle of justice can be the basis for this reformulation.